Local Analogs of Primordial Galaxies: In Search of Intermediate-mass Black Holes with JWST NIRSpec - Sara Doan; Shobita Satyapal; William Matzko; Nicholas P. Abel; Torsten Böker; Thomas Bohn; Gabriela Canalizo; Jenna M. Cann; Jacqueline Fischer; Stephanie LaMassa; Suzanne C. Madden; Jeffrey D. McKaig; et al. (The Astrophysical Journal)
Local low-metallicity galaxies with signatures of possible accretion activity are ideal laboratories in which to search for the lowest-mass black holes and study their impact on the host galaxy. Here we present the first JWST NIRSpec IFS observations of SDSS J120122.30+021108.3, a nearby ( z = 0.00354) extremely metal-poor dwarf galaxy with no optical signatures of accretion activity but identified by the Wide-field Infrared Survey Explorer to have red mid-infrared (MIR) colors consistent with active galactic nuclei (AGNs). We identify over 100 lines between ∼1.7 and 5.2 μ m, an unresolved nuclear continuum source with an extremely steep spectral slope consistent with hot dust from an AGN ( F _ν ≈ ν ^−1.5 ), and a plethora of H i , He i , and H _2 lines, with no lines from heavier elements, CO or ice absorption features, or polycyclic aromatic hydrocarbons (PAHs). While the bright central unresolved source (≲5 pc) is suggestive of an AGN, there are no He ii lines or coronal lines identified in the spectrum, and, importantly, there is no evidence that the radiation field is harder in the nuclear source compared with surrounding regions. The emission-line spectrum can be explained by a young (<5 Myr) nuclear star cluster with stellar mass ∼3 × 10 ^4 M _⊙ , but the unresolved continuum source is more typical for a deeply embedded AGN powered by a black hole of minimum mass ∼1450 M _⊙ . These observations reveal that either a metal-poor stellar population can heat the dust to extremely high temperatures, a result that would have significant impact on the reliability of MIR color selection in AGN surveys and our understanding of the properties of the interstellar medium and young stars in metal-poor galaxies, or an accreting intermediate-mass black hole is deeply embedded and hidden even at near-infrared wavelengths.